Land banking in the control of urban development - Flechner, Harvey L. (New York : Praeger Publishers, 1974)
This study attempts to identify and examine the conceptual and practical issues of land banking on a metropolitan scale.
Includes bibliographical references: p. 119-123.
oif 06/03/2019
Loans
Keywords: Regional planning; Land use; Metropolitan areas; United States